Hypercalcemia, Renal Failure, and Skull Lytic Lesions - Muhamad Alhaj Moustafa MD; Justin L. Seningen MD; Hayan Jouni MD (SAGE Publishing, 2013)
The findings of hypercalcemia, skull lytic lesions, and renal failure are usually characteristic for multiple myeloma. We herein describe an interesting case of B-cell follicular lymphoma that presented with many features mimicking multiple myeloma.